Strain-Induced Control of Magnetic Anisotropy Energy in NbS2 Monolayer: First-Principles Study - Berton Maruli Siahaan; Afrioni Roma Rio (Jurnal Fisika Unand, 2023)
In this work, we investigate the strain controllability of magnetic anisotropy energy (MAE) in the monolayer form of niobium disulfide (NbS2) using density functional theory (DFT). Our calculation reveals a negative MAE of -1.82 meV, indicating a preference for spins to align in the in-plane directions (x or y). By systematically applying biaxial tensile strain to the NbS2 monolayer, ranging from 1% to 10%, we observe a linear relationship between strain and MAE. Interestingly, the strain-induced modulation of MAE leads to a remarkable phenomenon, where the easy axis of magnetization shifts from the in-plane to an out-of-plane orientation at a critical strain of 7%. This ability to switch the magnetic anisotropy by manipulating strain demonstrates the promising potential of NbS2 monolayer in the development of spintronic devices.